Isolated Splenic Metastases from Renal Cell Carcinoma 11 Years after Surgery - Davi dos Santos Romao; Natally Horvat; Marianne Castro Gonçalves; Emerson Shigueaki Abe; Rodrigo Blanco Dumarco; Publio Cesar Cavalcante Viana; Marcel Cerqueira Cesar Machado (Case Reports in Medicine)
Splenic metastases are rare and usually occur in cases of disseminated disease. We report a case of a patient who had isolated splenic metastases with a previous history of left nephrectomy due to a renal cell carcinoma 11 years before. The aim of this report is to describe the case and review the literature of isolated splenic metastases due to renal carcinoma. This case emphasizes the importance of considering splenic metastatic disease even after many years of diagnosis of renal cell carcinoma.